(untitled) (مجلة البحوث الأكاديمية, 2025)
Background:- : Acute appendicitis is the most common surgical emergency in the pediatric population. Accurate diagnosis is crucial to reduce negative appendectomy rates. This study evaluates the clinical presentation, imaging findings, and histopathological outcomes in children who underwent appendectomy. Methods:- : A retrospective analysis of 131 pediatric appendectomy cases ages (2–16 years) was conducted. Data on demographics, clinical signs, imaging, and histopathology were collected and correlated. Results: The male-to-female ratio was 2.2:1. The most frequent symptoms were right iliac fossa pain (86.3%), nausea (70.2%), vomiting (54.2%), anorexia (59.5%), and fever (45%). Ultrasound was performed in 89 cases and was positive in 83 (93.3%). CT scans were used in only 2 cases. Histopathology confirmed in 131 patients with a negative appendectomy rate of 23.6%. Conclusion: Strong clinical suspicion and imaging (ultrasound) showed high sensitivity. Histopathology remains the definitive diagnostic tool. Combining clinical and radiological findings can reduce unnecessary surgeries